2010
DOI: 10.1111/j.1559-1816.2010.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

The Objective Value of Subjective Value: A Multi‐Round Negotiation Study

Abstract: A 2‐round negotiation study provided evidence that positive feelings resulting from one negotiation can be economically rewarding in a second negotiation. Negotiators experiencing greater subjective value (SV)—that is, social, perceptual, and emotional outcomes from a negotiation—in Round 1 achieved greater individual and joint objective negotiation performance in Round 2, even with Round 1 economic outcomes controlled. Moreover, Round 1 SV predicted the desire to negotiate again with the same counterpart, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(114 citation statements)
references
References 52 publications
5
108
1
Order By: Relevance
“…Similarly, in a later study, the authors (Curhan, Elfenbein, & Eisenkraft, 2010) found a positive relation between subjective value at one time point and economic value at a later point. Moreover, one study examined the impact of concern for relationships in a real world context, where relationships could be long-term.…”
Section: Economic Implicationsmentioning
confidence: 97%
“…Similarly, in a later study, the authors (Curhan, Elfenbein, & Eisenkraft, 2010) found a positive relation between subjective value at one time point and economic value at a later point. Moreover, one study examined the impact of concern for relationships in a real world context, where relationships could be long-term.…”
Section: Economic Implicationsmentioning
confidence: 97%
“…Responses were measured on a 7-point scale, and a global subjective value score was formed based on average responses across all items (α = .80; see Curhan, Elfenbein, & Eisenkraft, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…Humans who have found the joy of living in peace continuously seek deep down what makes them more powerful and happier; that is, what creates the most "subjective value" for them (Curhan, Elfenbein, and Eisenkraft 2010). Because humans are social and political beings by nature, what they need most is the amiable company of others.…”
Section: The Outer Peace Negotiation Followsmentioning
confidence: 99%